2007
DOI: 10.1289/ehp.9712
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Efficiency and Equity Implications of Power Plant Air Pollution Control Strategies in the United States

Abstract: BackgroundIn deciding among competing approaches for emissions control, debates often hinge on the potential tradeoffs between efficiency and equity. However, previous health benefits analyses have not formally addressed both dimensions.ObjectivesWe modeled the public health benefits and the change in the spatial inequality of health risk for a number of hypothetical control scenarios for power plants in the United States to determine optimal control strategies.MethodsWe simulated various ways by which emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 22 publications
2
73
0
1
Order By: Relevance
“…This paper also informs the environmental justice literature. That literature is typically concerned with analysing which household types are more affected by environmental pollution (Krieg & Faber, 2004;Levy et al, 2007). Instead, we focus on which household types are more responsible for environmental pollution.…”
Section: Socioeconomic Distribution Of Emissions and Resource Use In mentioning
confidence: 99%
“…This paper also informs the environmental justice literature. That literature is typically concerned with analysing which household types are more affected by environmental pollution (Krieg & Faber, 2004;Levy et al, 2007). Instead, we focus on which household types are more responsible for environmental pollution.…”
Section: Socioeconomic Distribution Of Emissions and Resource Use In mentioning
confidence: 99%
“…For example, a city wishing to analyze its air pollution could gather data on both pollution concentrations and on the pollution emissions of all major polluters. The concentrations could then be allocated to individual polluters using techniques like source-receptor matrices (Levy et al, 2007). 15 An analysis similar to our disaggregate analysis could then be conducted where the allocated concentrations data would be used in place of electricity and the emissions of the individual polluters used in place of our inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research has suggested that targeting environmental regulations to improve conditions for those who are most negatively impacted by environmental hazards can improve overall outcomes at the population level. For example, Levy et al (53) considered both the equity and efficiency benefits of a suite of hypothetical rollouts of emissions-control technology at power plants in the United States; they found that reductions in spatial inequality in mortality associated with emissions of SO 2 and fine particulate matter correlated with higher total reductions in mortality. A later study looking at controls on tail-pipe emissions on public buses in Boston drew similar conclusions (52).…”
Section: Implications For Research and Practicementioning
confidence: 99%